Long‐term effects of two 24‐hour moisturizing products on skin barrier structure and function: A biometric and molecular study. Issue 2 (6th June 2021) - Samadi, Aniseh; Nasrollahi, Saman Ahmad; Rostami, Mahmoud Nateghi; Rezagholi, Zahra; Abolghasemi, Farideh; Firooz, Alireza
Abstract: Introduction: Recently, there are a few moisturizers showing hydrating effects up to 24 hours after single application. Aquaporin 3 might be associated with the degree of skin hydration. We aimed to assess the effects of two brands of 24‐hour moisturizers on the skin barrier function, as well as the AQP3 gene expression. Method: Two moisturizers were applied once daily by 20 participants age 36.15 ± 9.55 years. Upper right and left forearms were randomly assigned to application of each product, whereas the right lower forearm served as control site for application of a cream base formulation. Biophysical assessments including trans epidermal water loss (TEWL), skin hydration, pH, surface lipids, and elasticity parameters were performed before intervention, 1, 4, and 24 hours after single application, following 2 weeks daily application and 1 week after termination of use. Also 5‐mm punch biopsies were performed from application sites of product B and cream base formulation in for five participants after 2 weeks of application. Results: A single treatment with both products led to 24‐hour increase in skin moisture in comparison with the control site ( P ‐value <.01). Daily application of both products for 14 days also led to significant improvement in skin moisture ( P ‐value <.01), TEWL ( P ‐value <.01), and elasticity parameters. The increase in skin hydration was associated with upregulation of AQP3 gene expression in treated area for one of the formulations ( P ‐value = .04). Conclusion: The tested 24‐hour moisturizers only need to be applied once daily to improve skin barrier function and hydration and up‐regulate AQP3 mRNA expression.